High‐intensity vs. sham inspiratory muscle training in patients with chronic heart failure: a prospective randomized trial. (August 2013) - Marco, Ester; Ramírez‐Sarmiento, Alba L.; Coloma, Ana; Sartor, Monique; Comin‐Colet, Josep; Vila, Joan; Enjuanes, Cristina; Bruguera, Jordi; Escalada, Ferran; Gea, Joaquim; Orozco‐Levi, Mauricio
<x xml:space="preserve">Abstract</x> Aims The purpose of this study was to evaluate the effectiveness, feasibility, and safety of a 4‐week high‐intensity inspiratory muscle training (hi‐IMT) in patients with chronic heart failure (CHF). Methods and results A double‐blind randomized clinical trial was carried out in 22 patients with CHF. Participants were assigned to the hi‐IMT or sham‐IMT group. The trainer device was a prototype of the Orygen‐Dual Valve®. The training workloads were adjusted weekly at the inspiratory pressure which allowed the performance of 10 consecutive maximal repetitions (10RM). Main outcomes were strength and endurance of the respiratory muscles assessed by maximal respiratory pressures (PImax and PEmax) and a 10RM manoeuvre, respectively. Twenty‐one patients presented impairment in respiratory muscle strength and endurance. Patients in the hi‐IMT group showed a significant improvement in both strength and endurance: inspiratory muscle strength in the intervention group increased 57.2% compared with 25.9% in the control group (P = 0.001). The percentage change in endurance was 72.7% for the hi‐IMT group compared with 18.2% in the sham‐IMT group (P < 0.001). No adverse effects occurred during the intervention. Conclusion A 4‐week hi‐IMT with the use of the Orygen‐Dual Valve® is shown to be an effective, feasible, and safe tool to improve weakness and fatigue of the inspiratory muscles. The key point of this study is to discuss immediate practical implications in terms of respiratory muscle dysfunction postulated as a potential prognostic factor and as an additional therapeutic target. Trials registration NCT01606553.